GENDER DIFFERENCES IN JAPANESE ELDERLY LEARNING MOTIVATION - Cahyani, Yesy Tri; Iskandar, Kurniawaty; Surajaya, I Ketut; Mizuno, Kosuke; Jumanto, Jumanto; Ligia, Emila (UI Scholars Hub, 2025)
Ageing is likely to become a 'gender issue' with a big number of women surviving into very old age in almost all the countries of the world. Japanese women have longer longevity than Japanese men. What is the secret behind the higher lifespan of Japanese women compared to Japanese men? Is it related to their ikigai? In this qualitative approach research, we chose the subjects as elderly men and women who participated in Easy English Conversation Courses in Kitakyushu Nenchousha Daigakkou (Kitakyushu Elder University). We assumed that to participate in Easy English Conversation Courses may change their life and enhance ikigai among the elderly, but there are gender differences in their elderly learning motivation. Understanding gender-specific factors related to ikigai in older adults could be beneficial in improving their overall well-being.